Biomarkers for drug-induced liver injury. Issue 4 (July 2010) - Watkins, Paul B
New biomarkers are needed in the clinic to distinguish drug-induced liver injury from other types of liver injuries, and to identify which specific drug is the culprit when drug-induced liver injury occurs in the setting of polypharmacy. There is also a need for new biomarkers that can be used in clinical trials to identify which new drugs in development have serious liver liabilities. When there are few alternative therapies available, biomarkers are needed to be able to identify patients susceptible to drug-induced liver injury from drugs known to have this liability. Developing and validating such biomarkers will require the establishment of well-annotated serum and urine banks from prospective clinical trials of drugs that have serious liver safety liabilities as well as those that do not.